THE ANALYSIS OF THE STUDENTS LEARNING DIFFICULTIES IN VOCABULARY AT SMP NEGERI 7 SATAP LANGOWAN - Ingratubun, Christin Febianti; Pelenkahu, Noldy; Liando, Nihta V. F. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The purpose of this research was to find out the students vocabulary learning difficulties and the factors that can affect learning difficulties in vocabulary at SMP Negeri 7 Satap Langowan. The type of research used is a qualitative method with a descriptive approach and use interview as data collection. Data analysis used in this research is data reduction, data presentation, and conclusion. The results of the research show that there are two aspects and factors that can cause students learning difficulties. The two aspects that can cause learning difficulties in English Vocabulary, namely: difficulty in pronunciation and meaning vocabulary. There also found internal and external factors that can affect the difficulty of learning English Vocabulary. Internal factors include attitude towards learning, learning motivation, learning concentration, saving the acquisition of learning outcomes, achievement or display of learning results, student self-confidence, study habits, and student aspiration. External factors include the school environment, family environment, and community environment.